2019
DOI: 10.1186/s40478-019-0760-0
|View full text |Cite
|
Sign up to set email alerts
|

COX2 expression is associated with proliferation and tumor extension in vestibular schwannoma but is not influenced by acetylsalicylic acid intake

Abstract: Acetylsalicylic acid has been linked to a lower risk for different cancer types, presumably through its inhibitory effect on cyclooxygenase 2. This has also been investigated in vestibular schwannomas with promising results suggesting an antiproliferative effect and recently the intake has been recommended for vestibular schwannomas as a conservative treatment option. We constructed tissue microarrays from paraffin-embedded tissue samples of 1048 vestibular schwannomas and analyzed the expression of cyclooxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Our data indicate that COX2-mediated inflammatory processes in vestibular schwannoma do not influence tumor growth. Thus, the recommendation to control tumor growth conservatively with acetyl salicylic acid via COX2 Regarding the preoperative tumor volume, relative higher COX2 expression is associated with larger vestibular schwannoma volume, which was already suggested in our prior study where a correlation of COX2 expression and the tumor extension (Hannover classification) was described [1]. An association of immune cell infiltration and vestibular schwannoma size has also been recently described [2] and could be a possible explanation for this finding.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our data indicate that COX2-mediated inflammatory processes in vestibular schwannoma do not influence tumor growth. Thus, the recommendation to control tumor growth conservatively with acetyl salicylic acid via COX2 Regarding the preoperative tumor volume, relative higher COX2 expression is associated with larger vestibular schwannoma volume, which was already suggested in our prior study where a correlation of COX2 expression and the tumor extension (Hannover classification) was described [1]. An association of immune cell infiltration and vestibular schwannoma size has also been recently described [2] and could be a possible explanation for this finding.…”
Section: Discussionsupporting
confidence: 64%
“…A recent study by our research group demonstrated a significant association of immunohistochemical detection of COX2 and proliferative marker expression (MIB1) in a large cohort of vestibular schwannomas [ 1 ]. We have now conducted volumetric tumor measurements of preoperative tumor size and growth in this cohort to further examine the possible proliferative effect of COX2 and proliferation marker MIB1 in VS.…”
Section: Introductionmentioning
confidence: 99%
“…Paracrine cellular communication between tumour-associated macrophages and Schwann cells seems to explain the decreased anti-tumour effect of tumour-associated macrophages. Furthermore, COX2 expression was significantly associated with higher MIB-1 expression [4]. Scar formation is a known component of prolonged inflammatory reactions, which is also mediated by COX2 [42].…”
Section: Mib-1 Proliferation Indexmentioning
confidence: 93%
“…In a 2019 study, tissue samples of 1048 tumours were analysed. It was discovered that while COX-2 expression increased with tumour proliferation, the use of acetylsalicylic acid did not alter COX-2 expression [85]. This study used tumour tissue retrospectively which can lend itself to selection bias since large tumours are more likely to be managed surgically.…”
Section: Emerging Treatmentsmentioning
confidence: 99%